The Effect of Ethical Sensitivity on Ethical Decision Making With Religiosity as Moderating Variable - Muslichah, Muslichah; Wiyarni, Wiyarni; Maria, Evi (International Review of Management and Marketing, 2018)
This study aims to investigate the effect of ethical sensitivity on ethical decision making with religiosity as moderating variable. This study used survey questionnaire in collecting data from five selected Universities (two public universities and three private colleges), namely STIE Asia, Universitas Negeri Malang, Universitas Kanjuruhan Malang (UNIKAMA), Universitas Islam Negeri (UIN) Maulana Malik Ibrahim Malang, and STIE Malangkucecwara. Samples of this study are the accounting students in the seventh semester. Based on the 202 responses received, this study found that there is a significant effect of ethical sensitivity on ethical decision making and religiosity on ethical decision making. Moreover, religiosity acts as a moderating variable on the relationship between moral sensitivity on ethical decision making. Keywords: Accounting, Ethical Sensitivity, Ethical Decision Making, Religiosity JEL Classifications: D8, D91, M41